2020
DOI: 10.3390/coatings10111112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Active Screen Plasma Power during Afterglow Nitrocarburizing on the Surface Modification of AISI 316L

Abstract: Active screen plasma nitrocarburizing (ASPNC) increases the surface hardness and lifetime of austenitic stainless steel without deteriorating its corrosion resistance. Using an active screen made of carbon opens up new technological possibilities that have not been exploited to date. In this study, the effect of screen power variation without bias application on resulting concentrations of process gas species and surface modification of AISI 316L steel was studied. The concentrations of gas species (e.g., HCN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The addition of CH 4 was about 10% of the feed gas, however, the measured densities are about 0.5%, which corresponds to a dissociation degree of 95% for CH 4 . The dissociation of CH 4 provides the carbon for generating HCN and CO molecules, the main carbonaceous species under these conditions, as expected from previous works [16,[20][21][22][23]. The sum of measured HCN and CO densities does not exceed 4% of nt , which accounts for approximately half of the carbon atoms introduced by the CH 4 flow.…”
Section: Overview Of the Measured Densitiessupporting
confidence: 84%
“…The addition of CH 4 was about 10% of the feed gas, however, the measured densities are about 0.5%, which corresponds to a dissociation degree of 95% for CH 4 . The dissociation of CH 4 provides the carbon for generating HCN and CO molecules, the main carbonaceous species under these conditions, as expected from previous works [16,[20][21][22][23]. The sum of measured HCN and CO densities does not exceed 4% of nt , which accounts for approximately half of the carbon atoms introduced by the CH 4 flow.…”
Section: Overview Of the Measured Densitiessupporting
confidence: 84%
“…Thereby, a significantly extended process window for a successful nitrocarburizing process was revealed. In particular, the nitrogen-hydrogen ratio [10] and the bias power at the steel components to be treated [11], as well as the power applied to the AS [12], were identified as factors influencing the resulting steel surface modifications. However, it was also demonstrated that the carbon-containing fraction within the resulting process gas can be varied only within small limits by lowering the plasma power at the carbon screen [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the nitrogen-hydrogen ratio [10] and the bias power at the steel components to be treated [11], as well as the power applied to the AS [12], were identified as factors influencing the resulting steel surface modifications. However, it was also demonstrated that the carbon-containing fraction within the resulting process gas can be varied only within small limits by lowering the plasma power at the carbon screen [12]. In order to exploit the possibilities of the extended process window of AS plasma nitrocarburizing (ASPNC) using a carbon AS for plain carbon and low-alloy steels, further concepts of process control and related parameters influencing the process itself need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows that the thickness of the dual S phase is 6.3 µm at 400 • C and 14.7 µm at 450 • C, which is similar to that of the S phase formed by the single carburizing process. Notably, a continuous process combining carburizing and nitriding for austenitic stainlesssteel plates increases the thickness of the S phase [38][39][40][41][42][43][44][45]. However, in this study, the amount of carbon increased during the first carburizing, which was conducted for a short time of 0.5 h in the continuous process and was less than the original solid-solution carbon content.…”
Section: Formation Mechanism Of the S Phase During A Continuous Plasm...mentioning
confidence: 61%
“…In this method, carbon diffuses from the surface to form an expanded austenitic phase, thus improving wear resistance similar to the nitriding S phase [30][31][32][33][34][35][36][37]. Furthermore, compared to only carburizing or nitriding, a continuous or simultaneous treatment that combines carburizing and nitriding can increase the thickness, hardness, and wear resistance of the S phase [38][39][40][41][42][43][44][45]. Therefore, low-temperature carburizing and combined treatments for AISI 316L stainless-steel-based tungsten carbide composite layers can be used to improve wear and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%